A Comparison of Urine Dilution Ability between Adult Dominant Polycystic Kidney Disease, Other Chronic Kidney Diseases, and Healthy Control Subjects: A Case-Control Study. (3rd December 2020) - Malmberg, M. H.; Mose, F. H.; Pedersen, E. B.; Bech, J. N.
Abstract : The final dilution of urine is regulated via aquaporin-2 water channels in the distal part of the nephron. It is unclear whether urine dilution ability in autosomal dominant polycystic kidney disease patients (ADPKD patients) differs from other patients with similar degree of impaired renal function (non-ADPKD patients). The purpose of this case control study was to measure urine dilution ability in ADPKD patients compared to non-ADPKD patients and healthy controls. Methods . Eighteen ADPKD, 16 non-ADPKD patients (both with chronic kidney disease, stage I-IV), and 18 healthy controls received an oral water load of 20 ml/kg body weight. Urine was collected in 7 consecutive periods. We measured free water clearance (CH2O ), urine osmolality, urine output, fractional excretion of sodium, urine aquaporin2 (u-AQP2), and urine epithelial sodium channel (u-ENaC). Blood samples were drawn four times (at baseline, 2 h, 4 h, and 6 hours after the water load) for analyses of plasma osmolality, vasopressin, renin, angiotensin II, and aldosterone. Brachial and central blood pressure was measured regularly during the test. Results . The three groups were age and gender matched, and the patient groups had similar renal function. One hour after water load, the ADPKD patients had an increased CH2O compared to non-ADPKD patients (2.97 ± 2.42 ml/min in ADPKD patients vs. 1.31 ± 1.50 ml/min in non-ADPKD patients, p 0.029 ). The reduction in u-AQP2 and u-ENaC occurred earlier in ADPKD than in non-ADPKD patients. Plasma concentrations of vasopressin, renin, angiotensin II, and aldosterone and blood pressure measurements did not show any differences that could explain the deviation in urine dilution capacity between the patient groups. Conclusions . ADPKD patients had a higher CH2O than non-ADPKD patients after an oral water load, and u-AQP2 and u-ENaC were more rapidly reduced than in non-ADPKD patients. Thus, urine-diluting capacity may be better preserved in ADPKD patients than in non-ADPKD patients.